Answer:
c,d
Step-by-step explanation:
![ab^{-3x}=a(b^{-3})^x=a(\frac{1}{b^3} )^x=a[(\frac{1}{b} )^3]^x\\=a(\frac{1}{b} )^{3x}](https://tex.z-dn.net/?f=ab%5E%7B-3x%7D%3Da%28b%5E%7B-3%7D%29%5Ex%3Da%28%5Cfrac%7B1%7D%7Bb%5E3%7D%20%29%5Ex%3Da%5B%28%5Cfrac%7B1%7D%7Bb%7D%20%29%5E3%5D%5Ex%5C%5C%3Da%28%5Cfrac%7B1%7D%7Bb%7D%20%29%5E%7B3x%7D)
The answer is C. 14.6.
By evaluate, they mean substitute in the values of x and y to find the total of the expression, so you get:
(3^2 + 4^3)/(3 + 2) = (9 + 64)/5 = 73/5 = 14.6
I hope this helps!
The expression coud be re written:
12x²y/2xy + 6xy/2xy + 4x²/2xy . Simplify numerator & denominator whenever it is possible:
6x-3+2x/y
<u><em>Good morning</em></u>,
Step-by-step explanation:
Look at the photo below for the Answer.
:)